2002
DOI: 10.1074/jbc.m111240200
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin-1 Is a Negative Regulator of Caveolae-mediated Endocytosis to the Endoplasmic Reticulum

Abstract: Caveolae are flask-shaped invaginations at the plasma membrane that constitute a subclass of detergent-resistant membrane domains enriched in cholesterol and sphingolipids and that express caveolin, a caveolar coat protein. Autocrine motility factor receptor (AMF-R) is stably localized to caveolae, and the cholesterol extracting reagent, methyl-␤-cyclodextrin, inhibits its internalization to the endoplasmic reticulum implicating caveolae in this distinct receptor-mediated endocytic pathway. Curiously, the rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
181
1
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(203 citation statements)
references
References 78 publications
18
181
1
3
Order By: Relevance
“…Our results are in apparent contrast to those of Nabi and coworkers who found that the overexpression of cav-1 negatively regulates the caveolar-mediated endocytosis of the autocrine motility factor receptor in NIH-3T3 cells (Le et al, 2002). One possible explanation is that there are distinct caveolar-mediated endocytic pathways with different characteristics (Le and Nabi, 2003).…”
Section: Bodipy-laccer Is Internalized By Caveolaecontrasting
confidence: 99%
“…Our results are in apparent contrast to those of Nabi and coworkers who found that the overexpression of cav-1 negatively regulates the caveolar-mediated endocytosis of the autocrine motility factor receptor in NIH-3T3 cells (Le et al, 2002). One possible explanation is that there are distinct caveolar-mediated endocytic pathways with different characteristics (Le and Nabi, 2003).…”
Section: Bodipy-laccer Is Internalized By Caveolaecontrasting
confidence: 99%
“…Endocytosis of agonistoccupied CCR5 probably follows a similar pathway. However, as suggested (Le et al, 2002;Thomsen et al, 2002), caveolae may exist in lymphocytes too, but may be rapidly converted into endocytic vesicles. It is possible that the enhanced CCR5 trafficking during immune cell activation is due in part to up regulation of caveolin (reviewed in Harris et al, 2002), which may disrupt rafts.…”
Section: Discussionmentioning
confidence: 94%
“…Recent reports have shown that both DRMs and glycolipid rafts are able to undergo endocytosis in the absence of caveolin. One caveat in interpreting this is that caveolae could still represent a brief vesicular intermediate in such cells, and evidence from using budding inhibitors and caveolin overexpression indicates that this may be the case (Le et al, 2002;Thomsen et al, 2002;Le and Nabi, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…En cas de déplétion, l'endocytose est inhibée en raison de la perturbation du contenu en cholestérol des cellules et de la désorganisation des domaines lipidiques à la membrane plasmique. Le même effet est observé lors d'une surexpression de CAV1 [22,23]. Plusieurs protéines « cargo » empruntant une voie cavéolaire, sans que celle-ci soit exclusive, ont été identifiées.…”
Section: Tableau I Caractéristiques Moléculaires Et Morphologiques Dunclassified